Northern Exposure COVID- 19 and Regional Inequalities in Health and Wealth - Bambra, Clare (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Whilst the COVID-19 pandemic affected all parts of the country, it did not do so equally. Northern England was hit the hardest, exposing more than ever the extent of regional inequalities in health and wealth. Using original data analysis from a wide range of sources, this book demonstrates how COVID-19 has impacted the country unequally in terms of mortality, health care, mental health, and the economy. The book provides a striking empirical overview of the impact of the pandemic on regional inequalities and explores why the North fared worse. It sets out what needs to be learnt from the pandemic to prevent regional inequality growing and to reduce inequalities in health and wealth in the future.